Converting eggplant biomass into multifunctional porous carbon electrodes for self-powered capacitive deionization. Issue 6 (14th May 2019) - Zhao, Cuijiao; Zhang, Shengbo; Sun, Na; Zhou, Hongjian; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract : A self-powered CDI system was constructed from porous carbon derived from eggplant for removal of salt and heavy metal ions. Abstract : Eggplant biomass was successfully converted into N, O-enriched hierarchical porous carbon materials as multifunctional electrodes for Zn–air battery-driven capacitive deionization via carbonization with potassium bicarbonate activation under a nitrogen atmosphere. The as-prepared N, O-enriched hierarchical porous carbon (NPC) electrode has a high N doping content (2.67 at%), oxygen-enriched chemical structure (surface oxygen content: 21.34 at%), hierarchical pore distribution (interconnected micro–meso–macropore system), high pore volume (0.72 cm 3 g −1 ), and large specific surface area (1226 m 2 g −1 ) as well as superior electroconductibility, which is advantageous for valid electrolyte approachability and rapid ion transmission to enhance the electrosorption capacity of carbon electrodes. These characteristics provided great salt adsorption capacity (SAC, 31.9 mg g −1 ) and excellent charge efficiency (CF, 60.3%) for capacitive deionization. Meanwhile, the NPC displays bifunctional electrocatalytic activities for the oxygen reduction reaction and oxygen evolution reaction, capable of constructing a rechargeable Zn–air battery with an open circuit voltage of 1.32 V. As a prototype integrated system, an NPC-800 constructed Zn–air battery was employed to power an NPC-800 symmetrical CDI device (denoted as a self-powered CDI system), showing comparable SAC and CF in the DC power driving mode. Furthermore, the self-powered CDI system also shows high removal efficiency for harmful heavy metal ions from water (99.1% for Pb 2+ and 97.9% for Cd 2+ ).